Pelatihan Akuntansi Sektor Publik Bagi Guru SMK, MAK dan SMA Bidang Ekonomi dan Bisnis di Wilayah Kabupaten Malang dan Blitar Bagian Selatan - Yanuarisa, Yesika; Djamhuri, Ali; Hidajah Ekowati, Wiwik; Nurhidayah, Nurhidayah (LPPM UMRI, 2023)
Public Sector Accounting (Government Accounting) education currently available in Indonesia is not at a satisfactory level. This is because the government accounting standard is a relatively new standard when compared to the private sector financial accounting standards embedded in the Financial Accounting Standards Statement (PSAK). The user has limited capabilities in implementing government accounting standards (SAP). This condition leads to a gap in understanding and mastering in the practice of government accounting standards. This also applies to teachers in the Senior High School (SMA). Public Sector Accounting Training for Vocational School (SMK) in the fields of Economics and Business, Vocational Madrasah Aliyah (MAK) and Senior High School (SMA) in the Malang District and Southern Blitar Region is a socialization of the standard of government accounting to be effective, intensify and extend the application of these standards from the preparation and improvement of qualifications for SMK, MAK, and SMA teachers. The method of training are preparation, socialization, implementation and evaluation. With this training, educational institutions will be able to produce graduates who have the ability or competence in the field of government accounting, so that the needs of accounting at various levels of government institutions e will be more easily met.